PENGARUH ONLINE CUSTOMER REVIEW, AFFILIATE MARKETING TERHADAP KEPUTUSAN PEMBELIAN DI TIKTOK SHOP - Saifuddin Zuhri; Nawari Nawari; M. Aktsar Al Mubarok (J-MACC, 2023)
This study aims to examine the influence of online customer reviews and affiliate marketing on purchasing decisions in TikTok Shop, specifically among students of the Faculty of Economics at Universitas Islam Darul ‘Ulum Lamongan (UNISDA). The study population comprised 1,243 students, with a sample size of 93 respondents selected using purposive sampling. The analytical methods used in this research include validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination test. The findings reveal that online customer reviews significantly and positively influence purchasing decisions, as indicated by a t-value of 3.593 > 1.987. Similarly, affiliate marketing has a significant and positive effect, with a t-value of 4.871 > 1.987. The simultaneous effect of both variables on purchasing decisions is also significant, as shown by an F-value of 36.1 > 2.71. The coefficient of determination (R²) is 0.446, indicating that 44.6% of the variance in purchasing decisions can be explained by online customer reviews and affiliate marketing.